Heart Rate Profile of Professional and Amateur Football Athletes in Bandung - Muhammad Rafi; Titing Nurhayati; Dian M Sari (Universitas Kristen Maranatha, 2018)
Routine physical exercise will provide a remarkable impact on the body,especially on cardiovascular system performance. This study aims to describe the heart rate profile of professional and amateur football athletes. This is a descriptive study with cross-sectional approach. Samples are taken through a total sampling approach in 34 athletes (17 professional football athletes from Persib U-19 team and 17 amateur football athletes from the Unpad Football Unit in Bandung). The average resting heart rate in professional football athletes is 70.29 times per minute while for amateur soccer athletes it is 88.47 times per minute. The mean post-step test heart rate in professional football athletes is 125.41 and in amateur athletes is 132.94. The average recovery time in professional football athletes is 2.06 minutes and in amateur athletes is 2.41 minutes. The study concludes that heart rate in the subject group of amateur soccer athletes is higher than the subject group of professional soccer athletes. Further research is needed to assess physical performance in both groups of athletes and evaluate the training programs that have been used.Keywords : amateur athletes, football, heart rate, professional athletes, recovery time, step testÂ